Využití síťování při práci se sociálně vyloučenou lokalitou - Šotola, Jaroslav; Zatloukal, Leoš (Univerzita Pardubice, 2010)
The starting point of this article is the belief that solution the causes of social exclusion requires the use of multidisciplinary collaboration. The text aims to introduce the concept of networking, which is usable for the theoretical considerations and practical applications of ways to be cooperation between different actors in the integration of socially excluded individuals and groups realized. The concept of networking includes case management, community work and the creation of thematic working groups.
Keywords: networking; case management; community work